A Case of Diagnostic Dilemma - LCH - Jyoti Arora; Pankaj Mehta; Vijay Kumar Roy; Vandita Sharma; Amit Kumar (Asian Journal of Medical Research, 2019)
LCH in the skin, bones, lymph nodes or pituitary gland usually gets better with treatment and is called low-risk. Some patients have involvement in the spleen, liver, bone marrow, lung and skeleton. This is called high-risk disease and may be more difficult to treat. This study was conducted in the Department of Physiology, SGT Medical College, Gurugram (Haryana). The result of this study revealed that Hepatitis along with above findings suggestive of langerhans cell histiocytosis. So this diagnosis was made in advanced stage of disease. This case had all the typical findings (symptoms & signs), but even then it took considerable time to come to the correct diagnosis of advanced stage of langerhans cell histiocytosis. Though presenting rarely, this case was interesting enough to discuss.